Propensities of Amino Acid Pairings in Secondary Structure of Globular Proteins - NACAR, CEVDET (SPRINGER, 2020)
A class of secondary structure prediction algorithms use the information from the statistics of the residue pairs found in secondary structural elements. Because the protein folding process is dominated by backbone hydrogen bonding, an approach based on backbone hydrogen-bonded residue pairings would improve the predicting capabilities of these class algorithms. The reliability of the prediction algorithms depends on the quality of the statistics, therefore, of the data set. In this study, it was aimed to determine the propensities of the backbone hydrogen-bonded residue pairings for secondary structural elements of alpha-helix and beta-sheet in globular proteins using a new and comprehensive data set created from the peptides deposited in Worldwide Protein Data Bank. A master data set including 4882 globular peptide chains with resolution better than 2.5 angstrom, sequence identity smaller than 25% and length of no shorter than 100 residues were created. Separate data sub sets also were created for helix and sheet structures from master set and each sub set includes 4594 and 4483 chains, respectively. Backbone hydrogen-bonded residue pairings in helices and sheets were detected and the propensities of them were represented as odds ratios (observed/[random or expected]) in matrices. Propensities assigned by this study to the residue pairings in secondary structural elements (as helix, overall strands, parallel strands and antiparallel strands) differ from the previous studies by 19 to 34%. These dissimilarities are important and they would cause further improvements in secondary structure prediction algorithms.
Keywords: Secondary structure prediction; Residue pairing; Residue propensity; Hydrogen bonding; ANTIPARALLEL BETA-SHEETS; ALPHA-HELICAL SEGMENTS; STRUCTURE PREDICTION; SEQUENCE; IDENTIFICATION; CONFORMATIONS; IMPROVEMENTS; RECOGNITION; PREFERENCES; ORIENTATION